Ways of Increasing of Linguodidactic Competence of the Humanitarian and Natural Directions Students (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is about how developing reading, writing and speaking skills. Using the new methods of teaching the students can how to use some words the difference between of words and word combinations.